Calcium, phosphor and alkaline phospatase value in bone graft calsium sulfat hemihydrate bioceramic application on animal bone defect (In Vivo Study) - Bahruddin Thalib; Mochammad D. Utama; Edy Machmud; Asmawati Asmawati; Steven Winarto; Nur Intang (Journal of Dentomaxillofacial Science, 2019)
Objective: This study aims to determine differences in the value of calcium, phosphor, and alkaline phosphatase in the blood of bone graft material which is applied to bone defectsMethods: 12Â male rabbits were divided into 4 groups, then defects were made in the femur bone with a diameter of 5mm. then each group was drawn with a vulnerable blood pre-operative time, 1 week, 3 weeks, and 6 weeks after surgery.Result: Average levels of calcium, alkaline phosphate and phosphorus in all treatment groups were higher than those in the control group.Conclusion: There were differences in calcium levels in test animals using bone graft Î±-calcium sulphate hemihydrates bioceramic on days 7th, 21st, and 42ndÂ post surgery.